NKG2D ligation relieves 2B4‐mediated NK‐cell self‐tolerance in mice. Issue 6 (16th April 2014) - Lee, Jung Eun; Lim, Seon Ah; Kim, Tae‐Jin; Kim, Kwanghee; Ng, Joanne; Kim, Yong Ho; Jang, In Jung; Oh, Seog Bae; Lee, June‐Chul; Yee, Cassian; Kumar, Vinay; Lee, Kyung‐Mi
<x xml:space="preserve">Abstract</x> Along with MHC class I (MHCI), 2B4 provides nonredundant NK‐cell inhibition in mice. The immunoregulatory role of 2B4 has been increasingly appreciated in models of tumor and viral infection, however, the interactions among 2B4, MHCI, and other activating NK‐cell receptors remain uncertain. Here, we dissect the influence of two distinct inhibitory pathways in modulating NK‐cell‐mediated control of tumors expressing strong activating ligands, including RAE‐1γ. In vitro cytotoxicity and in vivo peritoneal clearance assays using MHCI+CD48+ (RMA‐neo), MHCI+CD48+RAE‐1γ (RMA‐RAE‐1γ), MHCI−CD48+ (RMA‐S‐neo), and MHCI−CD48+RAE‐1γ (RMA‐S‐RAE‐1γ) tumor lines demonstrated that NKG2D activation supersedes the inhibitory effect of both 2B4‐ and MHCI‐mediated immune‐tolerance systems. Furthermore, 2B4KO mice subcutaneously challenged with RMA‐neo and RMA‐S‐neo exhibited reduced tumor growth and significantly prolonged survival compared with WT mice, implying that 2B4 is constitutively engaged in the NK‐cell tolerance mechanism in vivo. Nevertheless, the inhibitory effect of 2B4 is significantly attenuated when NK cells encountered highly stressed tumor cells expressing RAE‐1γ, resulting in an immune response shift toward NK‐cell activation and tumor regression. Therefore, our data highlight the importance of the 2B4‐mediated inhibitory system as an alternate self‐tolerance mechanism, whose role can be modulated by the strength of activating receptor signaling within the tumor microenvironment.